Fecal bacterial communities of wild-captured and stranded green turtles (Chelonia mydas) on the Great Barrier Reef. Issue 12 (23rd October 2017) - Ahasan, Md. Shamim; Waltzek, Thomas B.; Huerlimann, Roger; Ariel, Ellen
Abstract: Green turtles ( Chelonia mydas ) are endangered marine herbivores that break down food particles, primarily sea grasses, through microbial fermentation. However, the microbial community and its role in health and disease is still largely unexplored. In this study, we investigated and compared the fecal bacterial communities of eight wild-captured green turtles to four stranded turtles in the central Great Barrier Reef regions that include Bowen and Townsville. We used high-throughput sequencing analysis targeting the hypervariable V1–V3 regions of the bacterial 16S rRNA gene. At the phylum level, Firmicutes predominated among wild-captured green turtles, followed by Bacteroidetes and Proteobacteria. In contrast, Proteobacteria (Gammaproteobacteria) was the most significantly dominant phylum among all stranded turtles, followed by Bacteroidetes and Firmicutes. In addition, Fusobacteria was also significantly abundant in stranded turtles. No significant differences were found between the wild-captured turtles in Bowen and Townsville. At the family level, the core bacterial community consisted of 25 families that were identified in both the wild-captured and stranded green turtles, while two unique sets of 14 families each were only found in stranded or wild-captured turtles. The predominance of Bacteroides in all groups indicates the importance of these bacteria in turtle gut health. In terms of bacterial diversity and richness, wild-captured green turtles showed a higher bacterial diversity and richness compared with stranded turtles. The marked differences in the bacterial communities between wild-captured and stranded turtles suggest the possible dysbiosis in stranded turtles in addition to potential causal agents. Abstract : Comparative analysis of the fecal bacterial communities of wild-captured and stranded green turtles ( Chelonia mydas ).